The nickel aluminide coatings obtained on small holes produced with the EDD method - Trajer, Marcin (Strojniški vestnik, 2022)
Recently, airplane travel has become more affordable and thus more common. This has required engineers and scientists to spend thousands of hours on the development of new material and production technologies. High-pressure turbine (HPT) components are the most heavily loaded parts from the thermal, mechanical, and corrosion points of view. Therefore, both the material from which blades and vanes are cast as well as protective coatings are being constantly developed. Better material translates into longer and safer engine operation. Coatings maintain material structures within aggressive environments. However, despite the wide scope of development, there are areas that have not been investigated, one of which is electro-discharge drilling (EDD) machined cooling holes surface and its influence on environmental coating durability. In this paper, the EDD process impact on coating durability is shown. Process residuals, such as redeposited material and recast layers, result in coating inclusions. Oxidation testing also shows the relationship between the cooling hole diameter and coating durability.
Keywords: durability; EDD method; elektroerozijsko vrtanje; jet engines; nickel aluminide; prevleke; turbine blades; visokotlačne turbine